The Effect Of Leverage, Capital Intensity, And Sales Growth On Tax Avoidance With Independent Commissioners As Moderating Variables (Empirical Study On Manufacturing Companies Listed On The Indonesia Stock Exchange In 2017-2020) - Afrianti, Firdha; Uzliawat, Lia; Ayu Noorida S (Publisher Cv. Inara, 2022)
This study aims to determine the effect of leverage, capital intensity and sales growth on tax avoidance with independent commissioners as moderating variables. The independent variables in this study are leverage, capital intensity, and sales growth. The dependent variable in this study is tax avoidance. The moderating variable in this study is the independent commissioner. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in the 2017-2020 period. The sampling method used was purposive sampling and 53 companies were selected with a total sample of 212 research data. The analytical technique used is Moderated Regression Analysis (MRA) with SPSSv25 software. The results of this study indicate that leverage has a positive effect on tax avoidance, capital intensity has no effect on tax avoidance, sales growth has a positive effect on tax avoidance, the moderating variable of independent commissioners is unable to moderate the effect of leverage, capital intensity and sales growth on tax avoidance.